1986
DOI: 10.1111/j.1348-0421.1986.tb03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Differences in Pathogenicity between Two Variants of a Laboratory Strain of Herpes Simplex Virus Type 1

Abstract: The mechanisms responsible for the difference in neurovirulence to inbred mice between two variants of the Miyama strain of herpes simplex virus type 1 (HSV-1) were studied. After intraperitoneal (i.p.) inoculation, the +GC (LPV) variant reached the spinal cord and the brain, and caused death. Conversely, the -GCr variant lacked the ability to gain access to the central nervous system (CNS) after the same route of infection and failed to kill susceptible mice. The initial virus growth after i.p. inoculation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The complete lack of any histological lesions in the CNS of mice infected with HVP2ap strains suggests that either these viruses are unable to reach the CNS or, if they do, they are unable to replicate and produce pathological lesions. From studies on HSV, it appears that the amount of virus present at the peripheral site is directly related to the ability of the virus to enter sensory neurons and thus invade the CNS (29). The results of ELISA for detection of anti-HVP2 IgG in serum imply that HVP2ap isolates do not undergo sufficient replication at the site of inoculation to stimulate a robust immune response, suggesting that the block in HVP2ap infection occurs very early after inoculation.…”
Section: Discussionmentioning
confidence: 97%
“…The complete lack of any histological lesions in the CNS of mice infected with HVP2ap strains suggests that either these viruses are unable to reach the CNS or, if they do, they are unable to replicate and produce pathological lesions. From studies on HSV, it appears that the amount of virus present at the peripheral site is directly related to the ability of the virus to enter sensory neurons and thus invade the CNS (29). The results of ELISA for detection of anti-HVP2 IgG in serum imply that HVP2ap isolates do not undergo sufficient replication at the site of inoculation to stimulate a robust immune response, suggesting that the block in HVP2ap infection occurs very early after inoculation.…”
Section: Discussionmentioning
confidence: 97%
“…Since the level of virus in the lumbar spinal cord and associated DRGs represents the earliest point in the pathogenic process that is demonstrably different for HVP2ap and HVP2nv in wild-type 129 mice, it is likely that the ability of the host to delay and/or lessen entry of virus into the CNS plays a critical role in the dichotomous outcome of infection with the two HVP2 subtypes. In contrast, studies with HSV have shown that replication of the virus at the inoculation site appears to be important in that this replication amplifies the amount of virus thereby increasing the likelihood of viral entry into unmyelinated nerve fibers present in the skin to provide access to the CNS (Cunningham et al, 2006; Mossman and Ashkar, 2005; Yamada et al, 1986). While differences in the amount of HVP2ap vs. HVP2nv in skin were statistically significant only at 3 DPI, levels of HVP2ap were lower than those of HVP2nv at 2 and 4 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both viral dose and route of inoculation can influence the ability of a virus to establish a productive infection within a given host (Breshears, Eberle, and Ritchey, 2005; Weeks et al, 2000). In HSV infection of mice, the efficiency of viral replication at the peripheral site of infection is directly related to the ability of the virus to enter sensory neurons and invade the CNS (Yamada et al, 1986). However, once a virus has gained entry to a host organism, the most important host determinant of pathogenicity is likely the host innate immune response (Mossman and Ashkar, 2005; Simons and Nash, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…However, rMuIFN-J3 was not effective against the establishment and maintenance of latent infection. In previous studies [24,26], we have examined the mechanism responsible for the difference in pathogenicity to mice between virulent and attenuated variants of the Miyama strain of HSV-1. The extent of the initial viral growth in the peritoneal cavity was one of the most critical factors determining the outcome of IP infection of mice with HSV.…”
Section: Discussionmentioning
confidence: 99%